Finding Waqf Literacy Strategies for Millennials - Aisyah As-Salafiyah; Aam (International Journal of Waqf, 2022)
Waqf literacy is currently a challenge for waqf institutions, especially when the main target is the millennial generation, this is because the strategies used will certainly be different. Improving waqf literacy in the millennial generation has become a fairly popular study in indexed scientific journals. This study tries to map the development of published research in the field of waqf literacy. The research was conducted using VOSViewer software. The data analyzed were in the form of scientific research related to waqf literacy as many as 30 articles equipped with a Digital Object Identifier (DOI) published between 2011 and 2020. The results showed that the number of publications on the development of research results in the field of waqf literacy was quite a lot, with various research methods and countries of study object. The network visualization shows that the map of the development of waqf literacy research is divided into several clusters. Another finding based on the results of text mining, there are strategies related to waqf literacy in millennials that are the most studied. This study is the first to examine the scientific literature that discusses waqf literacy and identifies strategies that can be used to increase millennial waqf literacy.